PEMIDANAAN TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA STUDI KASUS PERKARA PIDANA NO. 07/PID-SUS-ANAK/2017/PN.PDG - Dewi Elvi Susanti (JCH (Jurnal Cendekia Hukum), 2019)
This study illustrates the basis and consideration of public prosecutors and judges in convicting children as perpetrators of crimes in a letter of claim and decision. There were two issues that would be examined, namely: a) What is the basis and consideration of the Public Prosecutor to file a complaint against the Child as a criminal in a case Number: 07/Pid.Sus-Anak/2017/Pn.Pdg, b) What is the basis and consideration of the Judge in making a decision on the Child as a criminal offender in the decision Number: 07/Pid.Sus-Anak/2017/Pn.Pdg, To discuss this problem a normative juridical method is used. From the results of the research obtained answers, a) the basis of the public prosecutor to file a claim against a child is Law Number 3 of 1997 concerning the Juvenile Court and Law Number 11 of 2012 concerning the Juvenile Justice System, and several Circular of the Indonesian Attorney General, while prosecutor's consideration General filed a claim in court No. 07/Pid.Sus-Anak/2017/Pn.Pdg was the fulfillment of the elements of the article being charged, things that incriminate and alleviate children's actions, the condition of parents of children, recommendations of correctional facilities (Bapas), paying attention to the interests of the community, victims and perpetrator; b) the basis of the judge in making a decision in case No. 07/Pid.Sus-Anak/2017/Pn.Pdg was Law Number 11 of 2012 concerning the Criminal Justice System of Children and was Law Number 3 of 1997 concerning Juvenile Courts. There were 2 (two) considerations the judge handed down the decision in case No. 07/Pid.Sus-Anak/2017/Pn.Pdg are juridical considerations and non-juridical considerations.